POLYCYSTIC OVARY SYNDROME AND METABOLIC SYNDROME - Kobuljonova Oydin Umidjon qizi (Scholar Express Journal, 2025)
Polycystic ovary syndrome and metabolic syndrome are considered important medical problems in modern medicine for women's health and the human body as a whole. Extensive information about the possible interrelationship of both diseases, their clinical manifestations, etiopathogenesis and the specificity of treatment methods is widely covered in research. This article provides a detailed analysis of the main features of polycystic ovary syndrome and metabolic syndrome, their relationship, diagnosis, clinical manifestations and treatment approaches
Keywords: polycystic ovary syndrome; metabolic syndrome; diagnostic treatment